PENGARUH KOMPENSASI FINANSIAL TERHADAP KINERJA KARYAWAN PT. HERO SUPERMARKET Tbk CABANG MTC GIANT PANAM PEKANBARU - Primadona, Dina Primadona Dina; Indrawati, Henny Indrawati Henny; Trisnawati, Fenny Trisnawati Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of financial compensation to employee performance of PT. Hero Supermarket Tbk MTC Branch Giant Panam Pekanbaru. The research was conducted at PT. Hero Supermarket Tbk MTC Branch Giant Panam Pekanbaru in May to July 2015. The research method used is descriptive quantitative method. The study population numbered 63 people. Sampling based Proportionate Stratified Random Sampling and data collected through a questionnaire, sample amounted to 54 people. Data collection instrument used was a questionnaire using a Likert scale for the independent variables: financial compensation (X) and the dependent variable: employee performance (Y). The data analysis technique used is a simple regression. Based on analysis of data that has been described that test the influence of financial compensation (X) on employee performance (Y) that produce significance 0.000 <0.05. Showed a significant difference between the financial compensation variable (independent variable) on employee performance variable (dependent) PT. Hero Supermarket Tbk MTC Branch Giant Panam Pekanbaru. If the greater the level of compensation provided by the company, the employee's performance will increase. Thus, the financial compensation variable give significant effect on performance variables as indicators of each variable is applied properly. So it can be concluded that the financial compensation accounted for 45.3% of the performance of employees of PT. Hero Supermarket Tbk MTC Branch Giant Panam Pekanbaru while the remaining 54.7% is influenced by other factors not examined.Keywords: influence, financial compensation, employee performance